2018
DOI: 10.1038/s41565-018-0086-2
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles as multimodal photon transducers of ionizing radiation

Abstract: In biomedical imaging, nanoparticles combined with radionuclides that generate Cerenkov luminescence are used in diagnostic imaging, photon-induced therapies, and as activatable probes. In these applications, the nanoparticle is often viewed as a carrier inert to ionizing radiation from the radionuclide. However, certain phenomena such as enhanced nanoparticle luminescence and generation of reactive oxygen species cannot be explained by only Cerenkov luminescence interactions with nanoparticles. Herein, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 49 publications
0
61
0
4
Order By: Relevance
“…A recent study by Pratt, Shaffer, Zhang, Drain, and Grimm (2018), however, offers an approach to eliminate the low luminescence yields of CR-PDT. The group examined the impacts of decay and secondary products from radionuclides on nanoscintillators.…”
Section: Cr-pdt Stimulated By Radioisotopesmentioning
confidence: 99%
“…A recent study by Pratt, Shaffer, Zhang, Drain, and Grimm (2018), however, offers an approach to eliminate the low luminescence yields of CR-PDT. The group examined the impacts of decay and secondary products from radionuclides on nanoscintillators.…”
Section: Cr-pdt Stimulated By Radioisotopesmentioning
confidence: 99%
“…Nanoparticles with higher optical crosssections than conventional fluorophores are ideal pairs for CL. [9] Pratt et al [6] have demonstrated that even though some nanoparticles are more luminescent than others,their combination with CR emitters can result in enhanced photoluminescence enhancement of up to 2500 times,a ne ffect that is different from chemiluminescence. Important considerations must be considered to achieve an adequate interaction between the nanoparticle and aradio- nuclide for CL-based applications.P rimarily,t he choice of nuclide will largely influence the CL intensity.I fC Lw ith ah igher intensity is desired, radiotracers that decay through higher energy emissions,such as 68 Ga or 90 Y, would be better choices than 18 For 64 Cu.…”
Section: Interaction Between Nanomaterials and Radionuclidesmentioning
confidence: 99%
“…[27] Recently, these X-rays were explored as potential SPECT agents.F or this,aSPECT instrument with an adjustable keV photon energy window is used. [6] Ap ioneering study by Pratt et al [6] foundt hat the characteristic photons emitted from nanoparticles made of elements with higher Z values, such as Eu, Gd, Au,a nd Bi, allow multimodal detection by X-ray imaging.T he authors also concluded that X-ray production increases with the atomic number of the nuclide in the NPs. [27] In that comprehensive study,t he authors performed in vitro studies to investigate X-rays generated by different types of nanoparticles when irradiated with different types of isotopes ( Figure 6a)aswell as to investigate the possibility of imaging those X-rays through SPECT ( Figure 6b).…”
Section: Gamma Scintillationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, Cerenkov luminescence imaging (CLI) was proposed as a novel imaging modality using the clinical radiopharmaceuticals . Previous studies have proven that radiopharmaceuticals emitting β + , β − and even α particles are capable to perform CLI, which significantly expands the type of probes for molecular imaging . By combining the advantages of both nuclear imaging and optical imaging, CLI owns the merits of high sensitivity, great imaging resolution and promising potential for clinical translation .…”
Section: Introductionmentioning
confidence: 99%